2013
DOI: 10.1186/1471-2164-14-18
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation and expression diversity between grain and sweet sorghum lines

Abstract: BackgroundBiological scientists have long sought after understanding how genes and their structural/functional changes contribute to morphological diversity. Though both grain (BT×623) and sweet (Keller) sorghum lines originated from the same species Sorghum bicolor L., they exhibit obvious phenotypic variations. However, the genome re-sequencing data revealed that they exhibited limited functional diversity in their encoding genes in a genome-wide level. The result raises the question how the obvious morpholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
24
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 51 publications
(66 reference statements)
7
24
1
Order By: Relevance
“…Differential expression between sweet and grain sorghum has recently been shown [21,40], and our results further validate this observation, with the majority of sugar-related genes showing differential expression among tissues and genotypes. For example, sweet and high biomass varieties showed consistently higher expression of SPS2 and SPS5, sugar phosphate enzymes thought to play significant roles in sucrose biosynthesis, compared to grain varieties (Figure 7).…”
Section: Resultssupporting
confidence: 88%
“…Differential expression between sweet and grain sorghum has recently been shown [21,40], and our results further validate this observation, with the majority of sugar-related genes showing differential expression among tissues and genotypes. For example, sweet and high biomass varieties showed consistently higher expression of SPS2 and SPS5, sugar phosphate enzymes thought to play significant roles in sucrose biosynthesis, compared to grain varieties (Figure 7).…”
Section: Resultssupporting
confidence: 88%
“…Similar SNP variations across 8 accessions have been reported through short-read genome sequencing of 8 diverse accessions of sorghum (Nelson et al 2011). Recently, Jiang et al (2013) adapted an integrative approach by using computational and experimental analyses to study the expression diversity between grain and sweet sorghum lines. It was observed that the genome sequences of grain and sweet sorghum exhibited considerable differences, but only limited divergence was observed in their functional genes, though more than 3,000 differentially expressed genes were detected between the grain and sweet sorghum varieties.…”
Section: Functional Diversity Analysis Using Gene and Est-based Markersmentioning
confidence: 91%
“…A total of 13 groups of variable size was recorded Billot et al (2013) number of alleles (29.7 %). Recently, Jiang et al (2013) adapted an integrative approach by using computational and experimental analyses to study the expression diversity between grain and sweet sorghum lines. African genotypes contributed 88.6 % of alleles, whereas those from the remaining parts of the world contributed 85.0 % of alleles.…”
Section: Functional Diversity Analysis Using Gene and Est-based Markersmentioning
confidence: 99%
“…SNPs may be present within coding or non-coding sequences of genes or in the intergenic regions between genes at different frequencies in different chromosome regions (Jiang 2013). SNP is the ultimate marker representing a single nucleotide difference between two individuals.…”
Section: Snpsmentioning
confidence: 99%